How do people with knee pain from osteoarthritis respond to a brief video delivering empowering education about the condition and its management?. Issue 8 (August 2021) - Egerton, Thorlene; McLachlan, Liam; Graham, Bridget; Bolton, Joanne; Setchell, Jenny; Short, Camille E.; Bryant, Christina; Bennell, Kim L.
Highlights: Typical beliefs about knee osteoarthritis often lead to activity avoidance. Information promoting empowerment for people with knee osteoarthritis is novel. Most people responded to the education with helpful emotions. Useful learning occurred although people still had many unanswered questions. Most people indicated new intentions to engage in effective lifestyle behaviours. Abstract: Objective: To evaluate responses by people with knee osteoarthritis to a brief educational video about their condition that aimed to empower and motivate effective self-management. The video content addressed psychosocial contributors to pain and barriers to behaviour change. Methods: A mixed methods design, including a survey and semi-structured interviews, was used to collect data from 118 people (46–83 years, 78% female) with knee osteoarthritis. Results: Quantitative data analysis showed the video was rated positively on 0–6 scales for enjoyability (mean 5.0), helpfulness (4.9), relevance (5.0) and believability (5.4). The majority would recommend the video (89%), learned new information (78%) and/or reported intentions to change behaviour (78%). A minority disliked aspects of the video (23%). The thematic analyses identified three main themes: Reactions to the video, including emotions; Learning from the video, including new knowledge and empowerment, but also unmet information needs or disagreement; and Intentions, including behaviour changes, cognitive changes and help seeking. Conclusion: Education about knee osteoarthritis with a focus on empowerment is well received by people with the condition, although some discordant views emerged. Practice implications: The educational video about knee osteoarthritis can be recommended to promote effective self-management and counteract potential drawbacks associated with biomedical-based education.